Familial hypercholesterolemia in primary care in Germany. Diabetes and cardiovascular risk evaluation: Targets and Essential Data for Commitment of Treatment (DETECT) study. (November 2017) - Schmidt, Nina; Schmidt, Burkhard; Dressel, Alexander; Gergei, Ingrid; Klotsche, Jens; Pieper, Lars; Scharnagl, Hubert; Kleber, Marcus E.; März, Winfried; Lehnert, Hendrik; Pittrow, David; Stalla, Günter; et al.
Abstract: Background and aims: Familial hypercholesterolemia (FH) is an inherited disorder of lipoprotein metabolism characterised by impaired removal of low-density lipoproteins (LDL) from the circulation, which leads to an increased risk of cardiovascular disease (CVD). This risk can be significantly lowered by early diagnosis and treatment. In Germany, reliable estimates of the prevalence of FH are lacking. We therefore examined the prevalence rate of FH in Germany in a primary care based cohort. Method: We utilized records of 4722 participants in the DETECT study, in whom complete data on blood lipids and medical history were available. Prevalence rates were assessed using the Dutch Lipid Clinics Network (DLCN) and the US-MEDPED criteria. We stratified for gender and age. Group differences were analyzed using Chi 2 and ANOVA tests. Results: Using the DLCN (probable or definite FH) and the US.MEDPED criteria yielded prevalence rates of 1:278 and 1:295, respectively. The established diagnostic scores used in this analysis identify different patients. In women below 50 years of age, the LDL-C concentration is lower than in men, leading to the possibility of under-diagnosing FH in this group because women under the age of 50 are less likely to reach a higher DLCN-Score. Conclusions: FH has a higher than expected prevalence in Germany. Clinical diagnostic algorithms may not be concordant. Highlights: FH has a higher than expected prevalence rate (1:300) in Germany. FH maybe underdiagnosed in women under 50 years of age due to generally lower LDL-C levels in this age group. The clinical diagnosis scores (DLCN, US-MEDPED) are not sufficient for a reliable diagnosis.